Career progression expectations, achievements, and retention in the classrooms: perceptions of public secondary school teachers in Tanzania - Reuben Bihu; Hillary Dachi (Discover Education)
Abstract This article explored public secondary school teachers’ entry career progression expectations and their perceived achievements of the expectations of teachers and school administrators in the classrooms in Bukoba District, Tanzania. The study employed a qualitative approach. Data collected from 62 respondents through interviews were subjected to analyses using UNESCO’s teacher career progression paths framework (in Teacher policy development guide, UNESCO, France, 2015). The results show the majority (44.44%) teachers’ entry career progression expectations were along the dual career progression path; 38.89% and 16.67% were along the vertical (i.e. direct) and horizontal career progression paths respectively. However, most of the participants in the vertical and dual career progression paths rated their perceived achievement of the expectations as low and non-achieving. Some reasons given for their low perceived levels of achievement of expectations were associated with appointments and promotions which were perceived to be effected without regard to transparency, professional impartiality, administrative, policy and legal frameworks. The study concludes that opportunities should be provided for experienced teachers and school administrators to have adequate exposure to the prospects of the progression including hierarchical positions of responsibilities they can aspire to in order not to move out or away from teaching. The article makes a number of recommendations to improve practice of career advancement for further research.